Maggot Black Soldier Fly (BSF) sebagai Solusi Atas Permasalahan Limbah Rumah Tangga dan Kelangkaan Pupuk di Desa Glagahwero - Sucipto, Irwanto; Resa Dwi Arianti; Cindy Dwi Anggarini; Nabilah Aulia Rohmah; Wildan Muhlison; Hari Purnomo; A. R. S. Ghozali; A. F. Hidayatullah (AKSILAR: Akselerasi Luaran Pengabdian Masyarakat, 2025)
Glagahwero Village has a lot of household waste that is disposed of at the TPS. People in these areas have waste problems that have not been managed optimally, as well as farmers who have fertilizer problems. The scarcity of fertilizer is suspected to occur in Glagahwero Village, this is due to the difficulty of distributing subsidized fertilizers. Based on the problem, a program was proposed with activities in the form of the introduction of maggot production cultivation from upstream to downstream where this innovation can overcome the problems that have been explained. The purpose of this service activity is to support the sustainability of agriculture in Glagahwero Village and the use of maggot residues as fertilizer to increase productivity, and income to all circles of the community, both farmers and PKK women in Glagahwero Village. The methods used in the implementation of the program consist of socialization and counseling activities on household waste management, maggot benefits, and kasgot. The activity went well with all participants active in the activity and asking questions. The results of the discussion were obtained that local villagers were interested in practicing maggot cultivation to reduce organic waste and solve the scarcity of fertilizers.